Perancangan Promosi Wisata Pantai Berbasis Videografi Sebagai Upaya Pengenalan Pariwisata Kabupaten Kotabaru Kalimantan Selatan - Ismail, Alban; Martono, Siswo; Latif, Yusmita Akhirul (Jurnal Art Nouveau, 2016)
Kotabaru District is one district in South Kalimantan Province is geographically quite unique, which in addition to having many islands, beaches and oceans as well as most of the island of Borneo also has mountains, valleys and plains as well as the persistence of the forest area or inland. This diversity is raised exotic nature so that it can be used as a tourist attraction. Therefore, as the introduction of South Kalimantan Kotabaru District tourism as well as to promote the tourism sector in Kotabaru, the authors put it in the form of beach-based tourism promotion design videography. The research method uses qualitative methods with data collection technique using observation, interviews, literature, and existing. The concept used in the design is the